Effects of lower limb muscle fatigue on gait performance and postural control among individuals with Parkinson's disease: a review of literature. (2nd November 2019) - Ghani, Halimatul Abd; Justine, Maria; Manaf, Haidzir
Abstract: Background: Fatigue is a common non-motor symptom of Parkinson's disease (PD). Individuals with PD experience difficulty in initiating movements, tremors, muscle rigidity and weakness, which progress as the disease worsens. These changes may lead to muscle fatigue, which may in turn affect gait performance and postural control (PC). There are few studies involving muscle fatigue affecting the gait performance and PC among individuals with PD. Objectives: Thus, this review aims to explore the existing evidence on how muscle fatigue affects gait performance and PC in PD. Major Findings: Five studies were included: three on gait performance, one on PC and one on gait performance and PC. Lower limb muscle fatigue alters the aspects of gait performance that may increase the risk of fall, e.g. inducing increased stride length, reduced stride duration and increased speed. However, no significant changes were observed in anticipatory PC among individuals with PD under fatigue condition. Conclusion: Further studies are suggested to explore this topic. A good understanding of gait characteristics can contribute to the development of tailored intervention strategies for individuals with PD.